Talent Management Philosophies and Practices in the Chinese Multinational Corporations: An Empirical Study - Liu, Yi; Pearson, Cecil; Chatterjee, Samir (Society for Global Business & Economic Development (SGBED), 2011)
A legacy of a centrally planned economy with a strong traditional bound culture, coupled with the dynamism injected by the arrival of international multinational corporations (MNCs), and even the rise of Chinese MNCs has created strong demands for talent in all spheres of China’s economic life. As Chinese companies extend their global reach, they increasingly face the complexities of personnel acquisition, including severe shortages of domestic managerialtalent, international brain drain of educated Chinese youth, and migration of managers from domestic Chinese companies to global MNCs. Against this background, the present study explores ways in which Chinese MNCs strategically integrate resources at the international level to attain global business success. The study findingindicated there is a crossvergence of talent management practices in Chinese MNCs, and such finding has potential to contribute to understanding how to overcome the identified barriers to the internationalisation process, especially in locating managerial talents.